INCLUSIVE TOURISM: WORLD EXPERIENCE AND PROSPECTS OF DEVELOPMENT IN UKRAINE (Development Service Industry Management, 2024)
The article is devoted to the study of the world experience of inclusive tourism, the state and prospects of its development in Ukraine, taking into account the consequences of the russian invasion. As a result of the research, it was found that the share of the planet's population with special needs is steadily increasing. Therefore, the world tourism industry is trying to be adapted to the corresponding changes. Accessibility is not only about human rights. It is also an additional business opportunity for destinations and companies to reach all visitors and increase their revenues. As a result of russia's military aggression in Ukraine, the number of people with disabilities has increased significantly. Currently, there is a very low supply of available services in the tourism industry in Ukraine, while the demand for such services is growing. There is a need to develop a strategy for the development of national accessible tourism. Given the circumstances, the national strategy should include: the development of transport infrastructure, a network of catering establishments and accommodation for tourists, an increase in the number of available tourist products, and the development of an information support system for available tourist services. Within the framework of financial support of the national strategy, it is proposed to use additional internal sources of funding. Namely: improving the practice of tourist tax administration; creation of local tourism development funds, to which proceeds from the payment of the tourist tax should be directed, respectively, with their subsequent use for improving accessibility. In order to generate additional funds that business entities could direct to improve accessibility, it is necessary to reduce the rate of the single tax for small businesses in the hospitality industry (to 1% of turnover). The implementation of the proposed steps will contribute to attracting additional funds to finance the strategy for the development of accessible tourism in Ukraine.
Keywords: inclusive tourism; access tourism; barrier-free tourism; universal tourism tourists with specific access requirements